Quality and viability of probiotics sold in handling pharmacies in Cascavel-PR (Research, Society and Development, 2021)
To be considered probiotic, a product must present viable cells, at the dose described on the label, until the expiry date and when handled in the form of capsules must follow the quality criteria set out in the legislation. Therefore, the aim of this study was to evaluate the quality of capsules handled with probiotics, as well as to verify the viability of microorganisms in three masterful pharmacies in the city of Cascavel-PR. The labeling of products, the average weight and cell viability. Microorganisms were identified using morpho-tinrial characteristics and catalase test. Only the pharmacy label 2 presented the description recommended by the legislation, however, despite the proposed shelf life, the manufacturer's report indicated that one of the raw materials was expired. The average weight was in compliance in all pharmacies. Regarding cell viability, there were differences in repetition and between pharmacies. In the repetition, pharmacy 1 did not show viable cell growth and Pharmacy 2 demonstrated a loss of viability when compared to the first trial. Pharmacy 3, when compared to other pharmacies, showed satisfactory growth. This study demonstrated that there is no strict quality control for the manipulation of capsules containing probiotics, compromising the quality and efficacy of the product. Thus, it is necessary to standardize these products according to their concentration, shelf life and excipients used, in order to ensure the best treatment for the patient.